Evaluation of the cross-immunity between Mycobacterium tuberculosis and Mycobacterium abscessus in vitro - Da Xu; Yujie Gu; Guilian Li; Ruihuan Wang; Shiqi Xiao; Hongyang Duan; Jingwei Jiang; Xiuqin Zhao; Kanglin Wan; Xinyue He; Haican Liu; Yongliang Lou (BMC Microbiology)
Abstract Mycobacterium tuberculosis (M. tuberculosis) and Mycobacterium abscessus (M. abscessus) are important pathogens that can cause lung diseases. Given the abundance of shared antigens between these two pathogens, evaluating the cross-immunization between Mycobacterium tuberculosis and Mycobacterium abscessus has implications for the assessment of tuberculosis vaccines based on nontuberculous mycobacteria (NTM). The whole-cell proteins of Mycobacterium abscessus were lysed via ultrasonication and then were subcutaneously injected into BALB/c mice either alone or mixed with adjuvant for three times at a 10-day interval. After the final immunization, cross-immune antigens were analysed via genomic comparison and Mycobacterium tuberculosis proteome microarrays. BALB/c mice splenic lymphocytes were stimulated with TB-PPD to assess the cross-immunity of the cellular immune response. The effect of cross-immunity on the growth of Mycobacterium tuberculosis was evaluated using a Mycobacterium tuberculosis growth inhibition assay. Despite the presence of 1,953 homologous gene clusters between Mycobacterium tuberculosis and Mycobacterium abscessus, only 302 Mycobacterium tuberculosis antigens exhibited cross-immunoreactivity after three immunizations. Compared with the PBS group, TB-PPD stimulation significantly increased the secretion of TNF-α, IL-4, and IL-6 by sensitized mouse splenic lymphocytes, and significantly affected the proliferation of IL-2+CD4 T and TNF-α+CD4 T cells in the immunized group (P < 0.05), but had no impact on IFN-γ and IFN-γ+ CD4 T cells. Furthermore, there was no significant difference in the proliferation of Mycobacterium tuberculosis between the immunized group and the PBS group in spleen cells. These data indicate that proteins from Mycobacterium abscessus are highly immunogenic in mice. However, the cross-immune response between Mycobacterium abscessus and Mycobacterium tuberculosis was inadequate to effectively inhibit the proliferation of Mycobacterium tuberculosis.